Dynamic Failure Properties of Sandstone Under Radial Gradient Stress and Cyclical Impact Loading - Wang, Shi-ming; Liu, Yun-si; Du, Kun; Zhou, Jian (Frontiers in Earth Science, 2019)
In order to analyze the dynamic fracture responses of surrounding rocks in underground space to cyclic impact loads, a series of dynamic compressive tests were conducted using hollow cylindrical and intact sandstone specimens under confining pressures corresponding to 5, 10 and 12 MPa, and the hollow cylindrical sandstone were subject to radial gradient stresses. In the study, the impact loads were applied via a large diameter split Hopkinson pressure bar (SHPB). The results indicated that the hollow cylindrical sandstone exhibited a lower dynamic strength and larger critical strain under radial gradient stress as compared to intact sandstone. The dynamic strength and critical strain of all rock specimens increased significantly with the increase of the number of impact loading, whereas the cumulative absorption energy decreased. Under impact loads with velocity of 11.89 m/s, the cumulative absorption energy increased with the increase of confining pressure. The impact load was a complex process of repeated tension and compression which easily affected the hollow cylindrical sandstone in the radial direction during cyclical impact loading, and the characteristics of zonal disintegration indicated dominant tensile failure and local shear failure. However, a compression-shear failure mode was observed under confining pressure for intact sandstone.